A preparation process for reducing the thermal expansion coefficient of copper clad laminate
By preparing a glue solution with a polyamino metal organic framework material and a specific resin combination, a 7628L semi-cured sheet was prepared by using glass cloth impregnation and baking process, and then a low thermal expansion coefficient copper clad plate was prepared according to the stacking and pressing process, which solved the problem of high thermal expansion coefficient of the existing copper clad plate and achieved a combination of low thermal expansion coefficient and high peel resistance.
Patent Information
- Application Number
- CN202211421652.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-14
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2042-11-14
AI Technical Summary
The existing copper clad plate has a high thermal expansion coefficient, which is difficult to meet the low requirements of precision instruments and instruments for thermal expansion coefficient.
By preparing a glue solution of a polyamino metal organic framework material and a specific resin combination, a 7628L semi-cured sheet was prepared using a glass cloth impregnation and baking process, and then a copper clad plate with a low thermal expansion coefficient was prepared according to the stacking and pressing process.
It effectively reduces the thermal expansion coefficient of copper clad plate and improves its peel resistance, making it suitable for the application of precision instruments and meters.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of copper clad laminates, in particular to a preparation process for reducing the thermal expansion coefficient of a copper clad laminate. Background Art
[0002] Copper clad laminate is a plate material made by impregnating electronic fiberglass cloth or other reinforcing materials with resin, covering one or both sides with copper foil and hot pressing. It is called copper clad laminate, or simply copper clad laminate.
[0003] With the diversified development of electronic and electrical products, copper clad laminates are used more and more in the fields of electronics industry, mechanical assembly, aerospace, new material development, etc., especially in precision instruments and meters, where the physical performance requirements of the products are getting higher and higher, especially the thermal expansion coefficient, that is, the Z-axis-CTE requirement, which requires that the size change with temperature is very small. Therefore, the thermal expansion coefficient needs to be fully considered in the production, processing and use of materials, and it is of great significance to measure the thermal expansion coefficient of materials. In order to adapt to the diversified market, it is worth studying the process of developing a process to reduce the thermal expansion coefficient while stabilizing product quality. Summary of the invention
[0004] The purpose of the present invention is to provide a preparation process for reducing the thermal expansion coefficient of a copper clad laminate, so as to solve the problems existing in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0006] A preparation process for reducing the thermal expansion coefficient of a copper clad laminate mainly includes the following process steps:
[0007] (1) Preparation of polyamino metal organic framework materials;
[0008] (2) KBJS-600A70 resin, tetrafunctional epoxy resin, dicyandiamide, coupling agent, filler, N,N-dimethylformamide, 2-methylimidazole, polyamino metal organic framework material, and aluminum hydroxide are mixed to prepare a glue solution;
[0009] (3) impregnating glass cloth with glue and then baking to obtain 7628L prepreg;
[0010] (4) Three 7628L prepregs were placed in the middle and two copper foils were placed on both sides to form a copper clad laminate with a low thermal expansion coefficient.
[0011] As an optimization, the preparation process for reducing the thermal expansion coefficient of the copper clad laminate includes the following process steps:
[0012] (1) Preparation of polyamino metal organic framework materials: zinc nitrate, 2-aminoterephthalic acid, pure water, anhydrous ethanol, and N,N-dimethylformamide are mixed in a mass ratio of 2:1:6:6:6 to 2:1:8:8:8, reacted in a reactor with polytetrafluoroethylene as a substrate at 130 to 150°C for 6 to 8 hours, then placed in a centrifuge, centrifuged at a speed of 6000 to 8000 r / min to obtain a product, washed the product with deionized water and anhydrous ethanol for 3 to 5 times each, and dried at 80 to 90°C for 5 to 6 hours to obtain a polyamino metal organic framework material;
[0013] (2) Mixing: KBJS-600A70 resin, tetrafunctional epoxy resin, dicyandiamide, coupling agent, filler, N,N-dimethylformamide are mixed uniformly in a mass ratio of 50:1:3:0.05:11:12-60:1:4:0.07:13:14, stirred at 30-40°C and 1200-1600 r / min for 2-3 h, and then 0.02-0.03 times the mass of KBJS-600A70 resin of 2-methylimidazole, 0.1-0.2 times the mass of KBJS-600A70 resin of polyamino metal organic framework material, and 0.2-0.3 times the mass of KBJS-600A70 resin of aluminum hydroxide are added and stirred for 2-3 h to obtain a glue solution;
[0014] (3) Baking: immerse the 7628L electronic grade glass cloth in the glue solution, and treat it with ultrasound at 40-50°C and 30-40kHz for 20-30 minutes, take it out and dry it at 80-90°C for 4-5 hours, immerse it in the glue solution again, let it stand at 40-50°C for 30-40 minutes, take it out and dry it at 80-90°C for 4-5 hours, and then bake it in a vertical dryer to obtain a 7628L prepreg;
[0015] (4) Stacking: Place three 7628L prepregs in the middle, place two copper foils with a thickness of 50 μm on the outside of the two sides, stack and press, and cool to room temperature to obtain a low thermal expansion coefficient copper clad laminate.
[0016] As an optimization, the tetrafunctional epoxy resin in step (2) is AG-80 tetrafunctional epoxy resin.
[0017] As an optimization, the tetrafunctional epoxy resin in step (2) is AG-80 tetrafunctional epoxy resin.
[0018] As an optimization, the coupling agent in step (2) is KBM-403 coupling agent.
[0019] As an optimization, the glass cloth in step (3) is 7628L electronic grade glass cloth.
[0020] As an optimization, the baking process parameters of step (3) are: baking temperature 190-210° C., baking time 2-3 min.
[0021] As an optimization, the copper foil in step (4) is HTE copper foil.
[0022] As an optimization, the process parameters of the pressing in step (4) are: heating rate 8-10°C / min, pressing temperature 230-240°C, pressing pressure 2.7-2.9MPa, vacuum value 18-20Torr, and pressing time 130-150min.
[0023] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0024] When preparing a copper-clad laminate with a low thermal expansion coefficient, the present invention firstly impregnates glass cloth with glue and then bakes it to obtain a 7628L prepreg, and then stacks and presses three 7628L prepregs in the middle and two copper foils on both sides to obtain a copper-clad laminate with a low thermal expansion coefficient.
[0025] Firstly, zinc nitrate and 2-aminoterephthalic acid are reacted to prepare a polyamino metal organic framework material, and KBJS-600A70 resin, tetrafunctional epoxy resin, dicyandiamide, coupling agent, filler, N,N-dimethylformamide, 2-methylimidazole, a polyamino metal organic framework material and aluminum hydroxide are mixed to prepare a glue solution. The amino groups on the polyamino metal organic framework material can react with the epoxy groups contained in the other components in the glue solution to form a cross-linked network structure, and the polyamino metal organic framework material has good mechanical properties, and the pore structure can be entangled with the other components in the glue solution, thereby improving the peeling resistance.
[0026] Secondly, by improving the stacking method and using the same glass cloth for stacking, the thermal expansion coefficient of the board can be effectively reduced. DETAILED DESCRIPTION
[0027] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0028] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index test methods for reducing the thermal expansion coefficient of the copper clad laminate prepared in the following examples are as follows:
[0029] Peel strength performance: The low thermal expansion coefficient copper clad laminates obtained in each embodiment and the comparative example materials were taken into the same size and shape, and the peel strength was tested.
[0030] Thermal expansion coefficient: The reduced thermal expansion coefficient copper clad laminate obtained in each embodiment and the comparative example material were taken into the same size and shape, and the thermal expansion coefficient was tested by TMA of model SDTA840.
[0031] Example 1
[0032] A preparation process for reducing the thermal expansion coefficient of a copper clad laminate, the preparation process for reducing the thermal expansion coefficient of a copper clad laminate mainly comprising the following process steps:
[0033] (1) Preparation of polyamino metal organic framework materials: zinc nitrate, 2-aminoterephthalic acid, pure water, anhydrous ethanol, and N,N-dimethylformamide are mixed in a mass ratio of 2:1:6:6:6, reacted in a reactor with polytetrafluoroethylene as a substrate at 130°C for 8 hours, then placed in a centrifuge, and centrifuged at a speed of 6000 r / min to obtain a product, the product is washed with deionized water and anhydrous ethanol for 3 to 5 times each, and dried at 80 to 90°C for 5 to 6 hours to obtain a polyamino metal organic framework material;
[0034] (2) Mixing: KBJS-600A70 resin, AG-80 tetrafunctional epoxy resin, dicyandiamide, KBM-403 coupling agent, HC-600 filler, and N,N-dimethylformamide were mixed uniformly in a mass ratio of 50:1:3:0.05:11:12, stirred at 30-40°C and 1200 r / min for 3 h, and then 0.02 times the mass of KBJS-600A70 resin of 2-methylimidazole, 0.1 times the mass of KBJS-600A70 resin of polyamino metal organic framework material, and 0.2 times the mass of KBJS-600A70 resin of aluminum hydroxide were added and stirred for 3 h to obtain a glue solution;
[0035] (3) Baking: immerse the 7628L electronic grade glass cloth in the glue solution, and carry out ultrasonic treatment at 40°C and 30kHz for 30 minutes, take it out and dry it at 80°C for 5 hours, immerse it in the glue solution again, let it stand at 40°C for 40 minutes, take it out and dry it at 80-90°C for 4 hours, and then bake it in a vertical dryer at a baking temperature of 190°C for 3 minutes to obtain a 7628L prepreg.
[0036] (4) Stacking: Place three 7628L prepregs in the middle, and place two HTE copper foils with a thickness of 50 μm on the outside of both sides for stacking and pressing. The heating rate is 8°C / min, the pressing temperature is 230°C, the pressing pressure is 2.7 MPa, the vacuum value is 18 Torr, the pressing time is 150 min, and the laminate is cooled to room temperature to obtain a low thermal expansion coefficient copper clad laminate.
[0037] Example 2
[0038] A preparation process for reducing the thermal expansion coefficient of a copper clad laminate, the preparation process for reducing the thermal expansion coefficient of a copper clad laminate mainly comprising the following process steps:
[0039] (1) Preparation of polyamino metal organic framework materials: zinc nitrate, 2-aminoterephthalic acid, pure water, anhydrous ethanol, and N,N-dimethylformamide were mixed in a mass ratio of 2:1:7:7:7, reacted in a reactor with polytetrafluoroethylene as a substrate at 140°C for 7 hours, and then placed in a centrifuge and centrifuged at a speed of 7000 r / min to obtain a product. The product was washed with deionized water and anhydrous ethanol for 4 times each, and dried at 85°C for 5.5 hours to obtain a polyamino metal organic framework material;
[0040] (2) Mixing: KBJS-600A70 resin, AG-80 tetrafunctional epoxy resin, dicyandiamide, KBM-403 coupling agent, HC-600 filler, and N,N-dimethylformamide were mixed uniformly in a mass ratio of 55:1:3.5:0.06:12:13, stirred at 35°C and 1400 r / min for 2.5 h, and then 0.025 times the mass of KBJS-600A70 resin of 2-methylimidazole, 0.15 times the mass of KBJS-600A70 resin of polyamino metal organic framework material, and 0.25 times the mass of KBJS-600A70 resin of aluminum hydroxide were added and stirred for 2.5 h to obtain a glue solution;
[0041] (3) Baking: immerse the 7628L electronic grade glass cloth in the glue solution, and perform ultrasound at 45°C and 35kHz for 25 minutes. Take it out and dry it at 85°C for 4.5 hours. Then immerse it in the glue solution again, let it stand at 45°C for 35 minutes, take it out and dry it at 80-90°C for 4-5 hours. Then, bake it in a vertical dryer at a baking temperature of 190-210°C for 2-3 minutes to obtain a 7628L prepreg.
[0042] (4) Stacking: Place three 7628L prepregs in the middle, and place two HTE copper foils with a thickness of 50 μm on the outside of both sides for stacking and pressing. The heating rate is 9°C / min, the pressing temperature is 235°C, the pressing pressure is 2.8 MPa, the vacuum value is 19 Torr, the pressing time is 140 min, and the laminate is cooled to room temperature to obtain a low thermal expansion coefficient copper clad laminate.
[0043] Example 3
[0044] A preparation process for reducing the thermal expansion coefficient of a copper clad laminate, the preparation process for reducing the thermal expansion coefficient of a copper clad laminate mainly comprising the following process steps:
[0045] (1) Preparation of polyamino metal organic framework materials: zinc nitrate, 2-aminoterephthalic acid, pure water, anhydrous ethanol, and N,N-dimethylformamide were mixed in a mass ratio of 2:1:8:8:8, reacted in a reactor with polytetrafluoroethylene as a substrate at 130°C for 8 hours, and then placed in a centrifuge and centrifuged at 8000 r / min to obtain a product. The product was washed with deionized water and anhydrous ethanol for 3 times each, and dried at 90°C for 6 hours to obtain a polyamino metal organic framework material;
[0046] (2) Mixing: KBJS-600A70 resin, AG-80 tetrafunctional epoxy resin, dicyandiamide, KBM-403 coupling agent, HC-600 filler, and N,N-dimethylformamide were mixed evenly in a mass ratio of 60:1:4:0.07:13:14, stirred at 40°C and 1600 r / min for 2 h, and then 0.03 times the mass of KBJS-600A70 resin of 2-methylimidazole, 0.2 times the mass of KBJS-600A70 resin of polyamino metal organic framework material, and 0.3 times the mass of KBJS-600A70 resin of aluminum hydroxide were added and stirred for 2 h to obtain a glue solution.
[0047] (3) Baking: immerse the 7628L electronic grade glass cloth in the glue solution, and perform ultrasound at 50°C and 40kHz for 20 minutes. Take it out and dry it at 90°C for 4 hours. Then immerse it in the glue solution again, let it stand at 50°C for 30 minutes, take it out and dry it at 90°C for 4 hours. Then, bake it in a vertical dryer at a baking temperature of 210°C for 2 minutes to obtain a 7628L prepreg.
[0048] (4) Stacking: Place three 7628L prepregs in the middle and two HTE copper foils with a thickness of 50 μm on the outside of the two sides for stacking and pressing. The heating rate is 10°C / min, the pressing temperature is 240°C, the pressing pressure is 2.9 MPa, the vacuum value is 20 Torr, the pressing time is 130 min, and the laminate is cooled to room temperature to obtain a low thermal expansion coefficient copper clad laminate.
[0049] Comparative Example 1
[0050] A preparation process for reducing the thermal expansion coefficient of a copper clad laminate, the preparation process for reducing the thermal expansion coefficient of a copper clad laminate mainly comprising the following process steps:
[0051] (1) Mixing: KBJS-600A70 resin, AG-80 tetrafunctional epoxy resin, dicyandiamide, KBM-403 coupling agent, HC-600 filler, and N,N-dimethylformamide were mixed uniformly in a mass ratio of 55:1:3.5:0.06:12:13, stirred at 35°C and 1400 r / min for 2.5 h, and then 0.025 times the mass of KBJS-600A70 resin of 2-methylimidazole and 0.25 times the mass of KBJS-600A70 resin of aluminum hydroxide were added and stirred for 2.5 h to obtain a glue solution;
[0052] (2) Baking: immerse the 7628L electronic grade glass cloth in the glue solution, and perform ultrasound at 45°C and 35kHz for 25 minutes. Take it out and dry it at 85°C for 4.5 hours. Then immerse it in the glue solution again, let it stand at 45°C for 35 minutes, take it out and dry it at 80-90°C for 4-5 hours. Then, bake it in a vertical dryer at a baking temperature of 190-210°C for 2-3 minutes to obtain a 7628L prepreg.
[0053] (3) Stacking: Place three 7628L prepregs in the middle, and place two HTE copper foils with a thickness of 50 μm on the outside of both sides for stacking and pressing. The heating rate is 9°C / min, the pressing temperature is 235°C, the pressing pressure is 2.8 MPa, the vacuum value is 19 Torr, the pressing time is 140 min, and the laminate is cooled to room temperature to obtain a low thermal expansion coefficient copper clad laminate.
[0054] Comparative Example 2
[0055] A preparation process for reducing the thermal expansion coefficient of a copper clad laminate, the preparation process for reducing the thermal expansion coefficient of a copper clad laminate mainly comprising the following process steps:
[0056] (1) Preparation of polyamino metal organic framework materials: zinc nitrate, 2-aminoterephthalic acid, pure water, anhydrous ethanol, and N,N-dimethylformamide were mixed in a mass ratio of 2:1:7:7:7, reacted in a reactor with polytetrafluoroethylene as a substrate at 140°C for 7 hours, and then placed in a centrifuge and centrifuged at a speed of 7000 r / min to obtain a product. The product was washed with deionized water and anhydrous ethanol for 4 times each, and dried at 85°C for 5.5 hours to obtain a polyamino metal organic framework material;
[0057] (2) Mixing: KBJS-600A70 resin, AG-80 tetrafunctional epoxy resin, dicyandiamide, KBM-403 coupling agent, HC-600 filler, and N,N-dimethylformamide were mixed uniformly in a mass ratio of 55:1:3.5:0.06:12:13, stirred at 35°C and 1400 r / min for 2.5 h, and then 0.025 times the mass of KBJS-600A70 resin of 2-methylimidazole, 0.15 times the mass of KBJS-600A70 resin of polyamino metal organic framework material, and 0.25 times the mass of KBJS-600A70 resin of aluminum hydroxide were added and stirred for 2.5 h to obtain a glue solution;
[0058] (3) Baking: immerse 7628M electronic grade glass cloth and 3313 electronic grade glass cloth in glue solution, and carry out ultrasonic treatment at 45°C and 35kHz for 25 minutes, take out and dry at 85°C for 4.5 hours, immerse in glue solution again, and stand at 45°C for 35 minutes, take out and dry at 80-90°C for 4-5 hours, and then bake in a vertical dryer at a baking temperature of 190-210°C for 2-3 minutes to obtain 7628L prepreg and 3313 electronic grade glass cloth;
[0059] (4) Stacking: Take two pieces of 7628L prepregs, one piece of 3313 electronic grade glass cloth, and two pieces of HTE copper foil with a thickness of 50 μm, and stack and press them in the order of HTE copper foil-7628L prepreg-3313 electronic grade glass cloth-7628L prepreg-HTE copper foil. The heating rate is 9°C / min, the pressing temperature is 235°C, the pressing pressure is 2.8 MPa, the vacuum value is 19 Torr, the pressing time is 140 min, and the low thermal expansion coefficient copper clad laminate is obtained after cooling to room temperature.
[0060] Comparative Example 3
[0061] A preparation process for reducing the thermal expansion coefficient of a copper clad laminate, the preparation process for reducing the thermal expansion coefficient of a copper clad laminate mainly comprising the following process steps:
[0062] (1) Mixing: KBJS-600A70 resin, AG-80 tetrafunctional epoxy resin, dicyandiamide, KBM-403 coupling agent, HC-600 filler, and N,N-dimethylformamide were mixed uniformly in a mass ratio of 55:1:3.5:0.06:12:13, stirred at 35°C and 1400 r / min for 2.5 h, and then 0.025 times the mass of KBJS-600A70 resin of 2-methylimidazole and 0.25 times the mass of KBJS-600A70 resin of aluminum hydroxide were added and stirred for 2.5 h to obtain a glue solution;
[0063] (2) Baking: immerse 7628M electronic grade glass cloth and 3313 electronic grade glass cloth in glue solution, and carry out ultrasonic treatment at 45°C and 35kHz for 25 minutes, take out and dry at 85°C for 4.5 hours, immerse in glue solution again, and stand at 45°C for 35 minutes, take out and dry at 80-90°C for 4-5 hours, and then bake in a vertical dryer at a baking temperature of 190-210°C for 2-3 minutes to obtain 7628L prepreg and 3313 electronic grade glass cloth;
[0064] (3) Stacking: Take two pieces of 7628L prepregs, one piece of 3313 electronic grade glass cloth, and two pieces of HTE copper foil with a thickness of 50 μm, and stack and press them in the order of HTE copper foil-7628L prepreg-3313 electronic grade glass cloth-7628L prepreg-HTE copper foil. The heating rate is 9°C / min, the pressing temperature is 235°C, the pressing pressure is 2.8 MPa, the vacuum value is 19 Torr, the pressing time is 140 min, and the low thermal expansion coefficient copper clad laminate is obtained after cooling to room temperature.
[0065] Effect example
[0066] Table 1 below shows the performance analysis results of the peeling resistance and Z-axis expansion coefficient of the low thermal expansion coefficient copper clad laminates of Examples 1 to 3 of the present invention and Comparative Examples 1 to 3.
[0067] Table 1
[0068] Peel strength Z-axis expansion coefficient Peel strength Z-axis expansion coefficient Example 1 1.23N / mm 1.90% Comparative Example 1 1.03N / mm 2.41% Example 2 1.25N / mm 1.87% Comparative Example 2 1.22N / mm 2.56% Example 3 1.22N / mm 1.86% Comparative Example 3 1.00N / mm 2.88%
[0069] From the comparison of the experimental data of Examples 1 to 3 and Comparative Tables 1 to 3 in Table 1, it can be found that the low thermal expansion coefficient copper clad laminate prepared by the present invention has good peeling resistance and a low thermal expansion coefficient.
[0070] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 1, it can be found that the peeling strength of Examples 1, 2, and 3 is higher than that of Comparative Example 1, and the Z-axis expansion coefficient is lower, which indicates that when the polyamino metal organic framework material is added to the glue, the amino groups on the polyamino metal organic framework material can react with the epoxy groups contained in the other components in the glue to form a cross-linked network structure, and the polyamino metal organic framework material has good mechanical properties, and the pore structure can be entangled with the other components in the glue, thereby improving the peeling resistance; secondly, when heated, the lateral vibration of the benzene ring on the polyamino metal organic framework material causes the distance between the metal clusters at both ends to decrease and form shrinkage, thereby reducing the overall thermal expansion coefficient; from the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 1, it can be found that the Z-axis expansion coefficient of Examples 1, 2, and 3 is lower than that of Comparative Example 1, which indicates that by improving the stacking method and using the same glass cloth for stacking, the thermal expansion coefficient of the plate is effectively reduced.
[0071] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A preparation process for reducing the thermal expansion coefficient of a copper clad laminate, characterized in that: The main process steps include: (1) Preparation of polyamino metal organic framework materials; (2) KBJS-600A70 resin, tetrafunctional epoxy resin, dicyandiamide, coupling agent, filler, N,N-dimethylformamide, 2-methylimidazole, polyamino metal organic framework material, and aluminum hydroxide are mixed to prepare a glue solution; (3) impregnating glass cloth with glue and then baking to obtain 7628L prepreg; (4) Three 7628L prepregs were placed in the middle and two copper foils were placed on both sides to form a copper clad laminate with a low thermal expansion coefficient.
2. A preparation process for reducing the thermal expansion coefficient of a copper clad laminate according to claim 1, characterized in that: The preparation process for reducing the thermal expansion coefficient of the copper clad laminate comprises the following process steps: (1) Preparation of polyamino metal organic framework materials: zinc nitrate, 2-aminoterephthalic acid, pure water, anhydrous ethanol, and N,N-dimethylformamide are mixed in a mass ratio of 2:1:6:6:6 to 2:1:8:8:8, reacted in a reactor with polytetrafluoroethylene as a substrate at 130 to 150°C for 6 to 8 hours, then placed in a centrifuge, centrifuged at a speed of 6000 to 8000 r / min to obtain a product, washed the product with deionized water and anhydrous ethanol for 3 to 5 times each, and dried at 80 to 90°C for 5 to 6 hours to obtain a polyamino metal organic framework material; (2) Mixing: KBJS-600A70 resin, tetrafunctional epoxy resin, dicyandiamide, coupling agent, filler, N,N-dimethylformamide are mixed uniformly in a mass ratio of 50:1:3:0.05:11:12-60:1:4:0.07:13:14, stirred at 30-40°C and 1200-1600 r / min for 2-3 h, and then 0.02-0.03 times the mass of KBJS-600A70 resin of 2-methylimidazole, 0.1-0.2 times the mass of KBJS-600A70 resin of polyamino metal organic framework material, and 0.2-0.3 times the mass of KBJS-600A70 resin of aluminum hydroxide are added and stirred for 2-3 h to obtain a glue solution; (3) Baking: immerse the 7628L electronic grade glass cloth in the glue solution, and treat it with ultrasound at 40-50°C and 30-40kHz for 20-30 minutes, take it out and dry it at 80-90°C for 4-5 hours, immerse it in the glue solution again, let it stand at 40-50°C for 30-40 minutes, take it out and dry it at 80-90°C for 4-5 hours, and then bake it in a vertical dryer to obtain a 7628L prepreg; (4) Stacking: Place three 7628L prepregs in the middle, place two copper foils with a thickness of 50 μm on the outside of the two sides, stack and press, and cool to room temperature to obtain a low thermal expansion coefficient copper clad laminate.
3. A preparation process for reducing the thermal expansion coefficient of a copper clad laminate according to claim 2, characterized in that: The tetrafunctional epoxy resin in step (2) is AG-80 tetrafunctional epoxy resin.
4. A preparation process for reducing the thermal expansion coefficient of a copper clad laminate according to claim 2, characterized in that: The coupling agent in step (2) is KBM-403 coupling agent.
5. A preparation process for reducing the thermal expansion coefficient of a copper clad laminate according to claim 2, characterized in that: The filler in step (2) is HC-600 filler.
6. A preparation process for reducing the thermal expansion coefficient of a copper clad laminate according to claim 4, characterized in that: The glass cloth in step (3) is 7628L electronic grade glass cloth.
7. A preparation process for reducing the thermal expansion coefficient of a copper clad laminate according to claim 4, characterized in that: The baking process parameters of step (3) are: baking temperature 190-210° C., baking time 2-3 min.
8. A preparation process for reducing the thermal expansion coefficient of a copper clad laminate according to claim 4, characterized in that: The copper foil in step (4) is HTE copper foil.
9. A preparation process for reducing the thermal expansion coefficient of a copper clad laminate according to claim 4, characterized in that: The process parameters of the pressing in step (4) are: heating rate 8-10°C / min, pressing temperature 230-240°C, pressing pressure 2.7-2.9MPa, vacuum value 18-20Torr, and pressing time 130-150min.
Citation Information
Patent Citations
Manufacturing technology of CEM-3 type copper-clad plate
CN104626713A
Flame-retardant heat-resistant copper-clad plate and preparation method thereof
CN113172963A